Assessing The Effectiveness of University Public Relations in Crisis Management - Albert John Calilao; Auvielle Domingo; Reig Janncen Labaro; Allyza Joy Pascua (People and Behavior Analysis, 2024)
Among organizational challenges, the pivotal role of Public Relations (PR) in mitigating crises becomes obvious. PR endeavors significantly influence stakeholder perceptions, institutional reputation, and sustained prosperity. Even venerable academic institutions contend with multifaceted risks that encompass natural phenomena, student activism, and scholarly debates. This research investigates the effectiveness of Northwestern University’s Public Relations (PR) program in crisis management, contributing significantly to both academic understanding and practical applications. Grounded in Social Constructionism, this study explores how shared perceptions influence crisis management outcomes, aiming to identify strengths and areas for improvement. Focusing on the crisis management effectiveness of the Philippines University, this research evaluates its capabilities in crisis handling, public perception management, and communication during challenging situations. Employing quantitative methods, the study involved 405 participants, including students and members of the Public Information Offices, reflecting a balanced representation across demographics. Students and Public Information Office members show nuanced but aligned perspectives, with high ratings for crisis planning, communication, media relations, and social media management. The proposed Public Relations in Crisis Management Program suggests strategic initiatives for crisis exercises, internal communication enhancements, media relationship building, and improved social media engagement. Positive perceptions underscore the organization’s crisis management strengths, providing a foundation for strategic program development. These interventions enhance organizational resilience by supporting continuous improvement and proactive crisis management. In conclusion, this study bridges the academic-practical gap in crisis management, affirming the organization’s adeptness and emphasizing the pivotal role of effective communication and engagement strategies. The proposed interventions offer actionable recommendations for further strengthening crisis management and highlight PR’s vital role in ensuring preparedness and resilience.